Developing English Learning Skills in the 21st Century - Sopajorn, Sakdipong (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
Learning skills in 21st Century is changing learning system from Curriculum, Time-slotted and Classroom into Projects, On-demand and Global Community system. Every learning process must be changed at all, such as teachers have to change themselves to be a coach and facilitator to their students for development learning skills. Thinking and analysis process is more necessary than recitation that focus on showing the opinion and seeking knowledge by themselves through basic life skills. In 21st Century the learners must have these skills; reading, writing and arithmetic, especially language environment must be suitable for learning skills that should be stimulated, created and recommended to successful goal. Thus teachers will know how to integrate and technique understanding among all students and look for the way to develop language skills that focuses on English language. All of teachers who teaches in school have to change and apply their teaching technique and emphasize listening and speaking skills more than repetition on grammar and vocabulary. They should also provide opportunities to the learners for practicing critical thinking, reading and speaking skills that is suitable with the learner by the time.